Polydopamine-induced hydroxyapatite coating facilitates hydroxyapatite/polyamide 66 implant osteogenesis: an in vitro and in vivo evaluation - Xu Y (Dove Medical Press, 2018)
Yanan Xu,1 Hong Li,2 Jieming Wu,3 Qiming Yang,1 Dianming Jiang,4 Bo Qiao1 1Department of Orthopedics, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Research Center for Nano-Biomaterials, Analytical and Testing Center, Sichuan University, Chengdu, People’s Republic of China; 3Office of Teaching Affairs, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 4Department of Orthopedics, The Third Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China Background: Hydroxyapatite/polyamide 66 (HA/P66) has been clinically used for several years owing to its good biocompatibility and bioactivity. However, it has been found that the osseointegration process of the HA/P66 implant takes a large amount of time because of the small amount of HA on its surface.Methods: To increase the amount of HA and aid faster osseointegration, we prepared a HA coating using a biomimetic process assisted by polydopamine (PDA) on the HA/P66 substrate. The surface properties of the substrate modified by PDA and HA were characterized, and the capacity of biomaterials for osteogenic induction was investigated both in vitro and in vivo. Results: The HA coating was successfully prepared on the HA/P66 substrate and verified by X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and X-ray diffraction (XRD). The HA coating remained firmly attached to the underlying PDA-HA/P66 substrate even after strong ultrasound treatment for 1 h, and the calcium and phosphorus of the HA coating was continuously released in vitro in a slow manner. The formation of the HA coating on the PDA film greatly increased the hydrophilicity and surface roughness of HA/P66. In cell-based experiments, as compared with the HA/P66 substrate, the HA coating formation on the PDA film could facilitate the functions of C3H10T1/2 cells, including cell adhesion, proliferation, spreading, alkaline phosphatase activity, calcium nodule formation, and expression of osteogenic differentiation-related proteins. In addition, the HA/P66 scaffolds modified with PDA and HA coatings were implanted in rabbit femoral condyles. At 8 weeks after surgery, micro-computed tomography scanning (micro-CT) and hematoxylin–eosin (HE) staining revealed that more new bones were formed around the HA/P66 scaffold that was modified with a PDA-assisted HA coating. Conclusion: These results indicate that the preparation of a PDA-assisted HA coating by using a biomimetic process significantly improves the capacity of biomaterials for osteogenic induction. Keywords: hydroxyapatite, polydopamine, hydroxyapatite/polyamide 66, surface modification, osteogenic induction